SEDIAAN NANOPARTIKEL KITOSAN EKSTRAK IKAN GABUS (CHANNA STRIATA) DAN UJI AKTIVITAS ALBUMIN TERHADAP PENYEMBUHAN LUKA PASCA PENCABUTAN GIGI - naning k utami; metty amperawati (Politeknik Kementerian Kesehatan Banjarmasin, 2020)
Cork fish (Channastriatus) are commonly found in river waters in South Kalimantan. said that cork fish gel extract was better than bloated fish gel extract, because of the closure of wounds after tooth extraction in white rats. The general purpose of this study was to determine the preparation of chitosan nanoparticles of cork fish extract (Channa Striata) and albumin activity test for healing of post-extraction wounds, while the specific purpose was to find out: 1). The optimal preparation based on the ratio of chitosan to extract, the ratio of tripolyphosphate used, and the difference in pH at the chitosan dissolution, 2). Physical characteristics of cork fish extract nanoparticles and 3). Nanoparticles extract activity of the album against the healing of post extraction wounds. The research method is experimental, research by testing cork fish nanoparticles on wound healing after tooth extraction which is divided into 2 (two) groups, namely control and treatment. Research sites in the Asthma Center Clinic and in the Pharmacology laboratory. Taking accidental sampling. The dependent variable is wound healing, the independent variable is Cork Fish Nanoparticles. T Statistical test results showed that the activity of chitosan nanoparticles albumin extract of cork fish on wound healing after tooth extraction was faster than those without treatment. It is recommended that the formulation of cork fish extract nanoparticles can be made in the form of mouthwash, variations in taste, and variations in concentration. Keywords: Chitosan Nanoparticles Cork Fish, Albumin, Wound Healing